SELF EFFICACY CHANGES IN COLLABORATIVE COURSE FOR INCLUSIVE EDUCATION PRESERVICE TEACHERS - Pujaningsih Pujaningsih; Unik Ambarwati (Jurnal Cakrawala Pendidikan, 2020)
The number of inclusive schools improves significantly in the last 10 years in Indonesia. However, there is a lack of effort to prepare future teachers so they have inadequate knowledge, skills, and experiences to provide education services for diverse students including students with special needs. This research examines the changes of Indonesian preservice teachers’ self-efficacy belief after being enrolled in a collaborative course that integrates between special education content and elementary education content. This study employed a mixed method approach for the analysis of questionnaire data from 34 preservice teachers and qualitative data of open-ended questions. The findings revealed that after being enrolled in a collaborative course, preservice teachers’ self-efficacy changed significantly (t34 = -2.16; p .05), especially in efficacy for instructional strategies (t34 = -2.73; p .05). The qualitative data also supported this finding based on three cases of preservice teachers who have different genders, previous experiences, and attitudes toward students with learning problems. Several recommendations for future collaborative courses and a new direction for the teacher preparation programs are discussed.